2020
DOI: 10.4037/aacnacc2020285
|View full text |Cite
|
Sign up to set email alerts
|

Moral Distress, Mattering, and Secondary Traumatic Stress in Provider Burnout: A Call for Moral Community

Abstract: Burnout incurs significant costs to health care organizations and professionals. Mattering, moral distress, and secondary traumatic stress are personal experiences linked to burnout and are byproducts of the organizations in which we work. This article conceptualizes health care organizations as moral communities—groups of people united by a common moral purpose to promote the well-being of others. We argue that health care organizations have a fundamental obligation to mitigate and prevent the costs of caring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 90 publications
(162 reference statements)
0
54
1
Order By: Relevance
“…Also, supported with the study conducted by Haizlip et al, 2020 who reported that, higher levels of mattering at work were associated with lower burnout and higher engagement. Epstein and et al (2020) who mentioned that, mattering, moral distress and secondary traumatic stress as they relate to burnout.…”
Section: Discussionmentioning
confidence: 99%
“…Also, supported with the study conducted by Haizlip et al, 2020 who reported that, higher levels of mattering at work were associated with lower burnout and higher engagement. Epstein and et al (2020) who mentioned that, mattering, moral distress and secondary traumatic stress as they relate to burnout.…”
Section: Discussionmentioning
confidence: 99%
“…When work and professional environments are not well organized and managed, they can have adverse consequences for workers that, far from dignifying them, exhaust them and consume their psychological resources. Burnout has become one of the most important psychosocial occupational hazards in today's society, generating significant costs for both individuals and organizations [1][2][3][4]. Although burnout was initially considered to be specific to professionals working in the care of people [5], later evidence has shown that this syndrome can develop among all types of professions and occupational groups [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Secondary traumatic stress (STS) describes the psychological experience of caring for traumatized or suffering others, and it is work related as a natural consequence of caring for traumatized people ( 13 ). STS is closely related to compassion fatigue (CF) and burnout ( 14 ). Stamm proposed Professional Quality of Life (ProQOL) model and she defined compassion fatigue (CF) as comprising both STS and burnout ( 15 ).…”
Section: Introductionmentioning
confidence: 99%